2000
DOI: 10.1046/j.1365-2249.2000.01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil feeding enhances lymphocyte proliferation but impairs virus-specific T lymphocyte cytotoxicity in mice following challenge with influenza virus

Abstract: The effect of a fish oil diet on virus‐specific cytotoxicity and lymphocyte proliferation was investigated. Mice were fed fish oil (17 g fish oil and 3 g sunflower/100 g) or beef tallow (17 g tallow and 3 g sunflower/100 g) diets for 14 days before intranasal challenge with influenza virus. At day 5 after infection, lung virus‐specific T lymphocyte, but not macrophage or natural killer (NK) cell, cytotoxicity was significantly lower in mice fed fish oil, while bronchial lymph node cell proliferation to virus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In fact, the study of this intracellular pathogen has increased our knowledge of the diverse interactions between this biological mediator and the innate and adaptive immune responses. Moreover, other investigations have also demonstrated the reduction of host immune resistance to different bacteria or viruses in animals fed polyunsaturated fatty acids (3,4,8,28,29).…”
Section: Discussionmentioning
confidence: 98%
“…In fact, the study of this intracellular pathogen has increased our knowledge of the diverse interactions between this biological mediator and the innate and adaptive immune responses. Moreover, other investigations have also demonstrated the reduction of host immune resistance to different bacteria or viruses in animals fed polyunsaturated fatty acids (3,4,8,28,29).…”
Section: Discussionmentioning
confidence: 98%
“…In this study, 18:33 increased serum antibodies to HEWL and the DTH reaction. Fish oils and 18:33 have been shown to increase antibody production in some [34,35] but not all studies [36,37]. Similarly, fish oils have been shown to increase the DTH reaction in some [38,39], but not all [40] studies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one major drawback identified thus far of fish oil consumption has been an increased susceptibility to pathogenic infection (53). For instance, a fish oil-feeding study in mice showed an impairment in CTL cytotoxicity upon infection with influenza virus (54). Further work is clearly required in understanding the benefits and drawbacks of dietary supplementation with PUFAs.…”
Section: Physiological Implicationsmentioning
confidence: 99%